Public Health, Primary Care, and Privatization - Arlesia Brock (University of North Florida, 2004)
Public health is an extremely vital but still little understood area of human endeavor. Traditionally, the public health system has been a vital resource for disadvantaged communities and families. Its unique ability to provide population based solutions to health problems has been essential to promoting and protecting the health of the underserved. However market forces are significantly changing the financial base and functional role of the public health departments. As a result, policymakers at all levels of government are looking for ways to provide leaner and more efficient delivery of services. A popular strategy is the privatization of public health services. This paper examines the changes in the public health system and primary care services in Florida's county health departments.